Strong and Tough MXene-Induced Bacterial Cellulose Macrofibers for AIoT Textile Electronics - Hao, Yi; Zhang, Zixuan; Chen, Yajun; Wang, Song; Tong, Yingjia; Lv, Pengfei; Wei, Qufu; Lee, Chengkuo (Nano-Micro Letters, 2026)
Textile electronics with extraordinary sensing capabilities holds significant potential in the Artificial Intelligence of Things (AIoT). However, little effort is paid to their mutual advantages of robust interfacial interactions, ultra-strong mechanical performance, and stability. Herein, we fabricate homogeneous and multifunctional core–shell macrofibers by integrating bridge-functionalized MXene/PEDOT:PSS conductive ink with aligned bacterial cellulose (BC). These resulting macrofibers feature mechanical properties (tensile strength of 433.2 MPa and the Young’s modulus of 25.9 GPa), exceptional electrical conductivity (10.05 S cm−1) and durable hydrophobicity. Such superior robustness allows for the fabrication of the macrofibers woven into textile-based triboelectric nanogenerator (PKT-TENG) and shows an impressive high-performance of a maximum open-circuit voltage of 272.54 V, short-circuit current of 14.56 μA and power density of 86.29 mW m−2, which successfully powers commercial electronics. As the proof-of-concept illustration, the macrofibers with durable hydrophobicity and high piezoresistive sensitivity are further employed for precepting diverse liquids that can simultaneously monitor their distinctive motion features via real-time resistance variation on the textile-based array. This work is expected to offer new insights into the design of advanced fibers with ultra-strong mechanical capabilities and high conductivity and provide an avenue for the development of textile electronics for high-performance sensing and intelligent manufacturing. Highlights: 1 PKT-TENG woven with K-MXene/PEDOT:PSS integrated bacterial cellulose (BC) via polydimethylsiloxane (PDMS) coating (PKMPBC) macrofibers were fabricated by bridging K-MXene/PEDOT:PSS ink with aligned BC macrofibers, then dip-coated with PDMS, showing high conductivity (10.05 S cm−1), high mechanical strength (433.8 MPa) and superior Young’s modules (25.9 GPa). 2 PKT-TENG integrated with PKMPBC macrofiebrs shows excellent triboelectric response and stability, delivering 86.29 mW m−2 power density to power an electronic watch and capacitors. 3 Resistance-sensitive PKMPBC macrofibers proved the capability of recognition for diverse liquid with precisely detection and fed back multifactor behaviors.